Intelligent Transport Systems - Martins, A.; Ferreira, J.; Ulpan; Kocian, A (2023)
This book constitutes the proceedings of the 6th International Conference on Intelligent Transport Systems, INTSYS 2022, which was held in Lisbon, Portugal, in December 15-16, 2022. With the globalization of trade and transportation and the consequent multi-modal solutions used, additional challenges are faced by organizations and countries. Intelligent Transport Systems make transport safer, more efficient, and more sustainable by applying information and communication technologies to all transportation modes. The 15 revised full papers in this book were selected from 45 submissions and are organized in three thematic sessions on smart city; transportation modes and AI; intelligent transportation and electric vehicles.Computer Science Informatics Conference Proceedings Research Applications